2018
DOI: 10.19082/7146
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tumor necrosis factor alpha (TNFα) and interleukin 6 level in gingival crevicular fluid during orthodontic tooth movement: a randomized split-mouth clinical trial

Abstract: BackgroundOrthodontic tooth movement (OTM) is based on induction of periodontal tissue remodeling. Mechanical tooth stimulation results in the release of pro-inflammatory mediators. These mediators cause bone resorption and deposition at the pressure and tension sites and play a role in OTM. Thus, assessment of chemical biomarkers can help determine the exact amount of load and its duration of application required for each tooth and select the most efficient treatment plan with minimal complications.ObjectiveT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Among these cytokines, IL‐1β and IL‐6, which induce the synthesis of nuclear factor‐κB receptor activating factor ligand (RANKL) in periodontal ligament fibroblasts to promote osteoclast differentiation, resulting in the development of RR, have been the most investigated (Kikuta, Yamaguchi, Shimizu, Yoshino, & Kasai, ; Kirschneck, Maurer, Wolf, Reicheneder, & Proff, ). Other cytokines, such as IL‐7, IL‐8, and TNF‐α, can also induce osteoclastogenesis and promote the function of osteoclasts (Ahuja et al, ; Padisar, Hashemi, Naseh, Nikfarjam, & Mohammadi, ). Although various inflammatory factors play a role in RR, the specific origins of these inflammatory factors are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these cytokines, IL‐1β and IL‐6, which induce the synthesis of nuclear factor‐κB receptor activating factor ligand (RANKL) in periodontal ligament fibroblasts to promote osteoclast differentiation, resulting in the development of RR, have been the most investigated (Kikuta, Yamaguchi, Shimizu, Yoshino, & Kasai, ; Kirschneck, Maurer, Wolf, Reicheneder, & Proff, ). Other cytokines, such as IL‐7, IL‐8, and TNF‐α, can also induce osteoclastogenesis and promote the function of osteoclasts (Ahuja et al, ; Padisar, Hashemi, Naseh, Nikfarjam, & Mohammadi, ). Although various inflammatory factors play a role in RR, the specific origins of these inflammatory factors are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…(D) Statistical analysis of differences in MCP-1 expression in the periodontium. *p < .05, **p < .01 IL-8, and TNF-α, can also induce osteoclastogenesis and promote the function of osteoclasts (Ahuja et al, 2017;Padisar, Hashemi, Naseh, Nikfarjam, & Mohammadi, 2018). Although various inflammatory factors play a role in RR, the specific origins of these inflammatory factors are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TNF-α is expressed in the PDL and alveolar bone during orthodontic tooth movement [ 64 , 65 ]. Moreover, in GCF studies during OTM, many reports have shown that PGE, IL-1, IL-6, IL-17, and TNF-α can be detected in compression and/or tension side [ 66 , 67 , 68 , 69 ]. Therefore, these inflammatory cytokines intricately intertwined with one another during OTM, and play important roles in bone remodeling.…”
Section: Inflammatory Mediators In Orthodontic Tooth Movementmentioning
confidence: 99%
“…Other authors also report a similar increase in TNFα in the initial 24-hour time interval vs. baseline [24,25]. It was also revealed that concentration of TNF-α in force area was higher than the control side [26]. TNF-α is expressed in the force-applied area of the tooth and has a significant role in mechanical tooth movement [27].…”
Section: Discussionmentioning
confidence: 68%
“…TNF-α is expressed in the force-applied area of the tooth and has a significant role in mechanical tooth movement [27]. Orthodontic tooth movement increases TNF-α in the area surrounding the periodontal tissue [26].…”
Section: Discussionmentioning
confidence: 99%